The persistence of modernism in the music and thought of Mathias Spahlinger - Smith, Neil T. (2017)
This thesis discusses the music and thought of one of Germany’s leading practitioners of contemporary music, composer Mathias Spahlinger. His work will be examined within the framework of studies of modernism in music, and aesthetics more widely, revealing a compositional approach that displays significant continuities with the practice of previous modernists, while also constituting a compellingly critical reinvention of many of their ideas. Through engaging with positions critical of previous modernist music, crucial debates in the composer’s music and thought will be identified, including the modes of listening assumed by modernist composers, implicit hierarchies in the thought and practice of modernist music, and issues of musical autonomy and political effect. In particular, Spahlinger’s unique exploration of the issue of musical autonomy will be considered from two differing perspectives in analyses of his breakthrough orchestral piece, passage/paysage (1990), and the choral work, in dem ganzen ocean von empfindungen eine welle absondern, sie anhalten (1985). It will be shown that these pieces rely on a form of expression in which abstract musical argument and political intention are merged to the point of indivisibility – and that this constitutes a crucial element of Spahlinger’s modernist project.